2007
DOI: 10.1007/s00246-007-9098-7
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Resistance in Children with Heart Disease at Risk for Thromboembolism: Prevalence and Possible Mechanisms

Abstract: Aspirin is used to prevent thromboembolism in children with heart disease without evidence supporting its efficacy. Studies in adults report a 5%-51% prevalence of aspirin resistance, yet the mechanisms involved are poorly understood. Our aims were to determine its prevalence in these children and to explore its possible mechanisms. One hundred twenty-three cardiac patients routinely receiving aspirin were prospectively enrolled. Platelet function was measured by Platelet Function Analyzer (PFA)-100 using epin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 27 publications
1
29
2
1
Order By: Relevance
“…Heistein et, al. (21) reported that the prevalence of aspirin resistance was 26% in children with congenital heart disease. The authors suggested that the resistance is not entirely due to lack of inhibition of platelet TXB2 production since alternative sources of TXB2 and thromboxane A2-independent mechanisms, such as ADP-induced platelet activation, may contribute to aspirin resistance.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Heistein et, al. (21) reported that the prevalence of aspirin resistance was 26% in children with congenital heart disease. The authors suggested that the resistance is not entirely due to lack of inhibition of platelet TXB2 production since alternative sources of TXB2 and thromboxane A2-independent mechanisms, such as ADP-induced platelet activation, may contribute to aspirin resistance.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…It is well known that aspirin exerts its antithrombotic effect to inhibit platelet aggregation (PAG) and reduce platelet activity, which is largely attributed to its irreversible inactivation of cyclooxygenase, leading to impaired platelet function (Cholette et al, 2010). It is important to note that most patients demonstrate an adequate response to 3-5 mg/kg/day of aspirin for 6 months, which is at present the dose generally recommended for the prophylaxis of thromboembolic events after interventional closure of ASD (Heistein et al, 2008). Nevertheless, a significant improvement has not been consistently found in response to doubling the dose of aspirin in those with a poor antiplatelet response, which lends additional evidence to demonstrate that increasing the aspirin dosage may not markedly affect its antiplatelet effects (Wiegand et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…The incidence rates were different among the types of heart diseases; cyanotic heart disease at 39.5%, acyanotic heart disease at 17.5% and no structural heart at 20%. These three groups were different in terms of age, weight and hemoglobin levels [31]. Therefore, the differences between incidence rates may depend upon the age, underlying diseases and method of diagnosis.…”
Section: Discussionmentioning
confidence: 97%